2002
DOI: 10.1016/s0022-3697(02)00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Successive phase transitions in a metal-ordered manganite perovskite YBaMn2O6

Abstract: Structural, magnetic and electric properties of a metal-ordered perovskite YBaMn 2 O 6 have been studied by means of powder X-ray diffraction, DSC, magnetic susceptibility, and electric resistivity. It is found that this material undergoes a 1st order structural phase transition at T c1 =520 K, from a pseudo orthorhombic (monoclinic) phase (T c1 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
85
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 10 publications
15
85
0
Order By: Relevance
“…Iodometric titration revealed a value of 0.97 (1) for the amount of excess oxygen, δ, in the O 2 -annealed sample. We may thus conclude in agreement with previous reports [17,20] that an essentially fully-oxygenated BaYMn 2 O 5+δ (with δ ≈ 1) phase has been obtained from the oxygen-depleted BaYMn 2 O 5+δ (with δ ≈ 0) sample by means of the low-temperature O 2 annealing.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Iodometric titration revealed a value of 0.97 (1) for the amount of excess oxygen, δ, in the O 2 -annealed sample. We may thus conclude in agreement with previous reports [17,20] that an essentially fully-oxygenated BaYMn 2 O 5+δ (with δ ≈ 1) phase has been obtained from the oxygen-depleted BaYMn 2 O 5+δ (with δ ≈ 0) sample by means of the low-temperature O 2 annealing.…”
Section: Resultssupporting
confidence: 93%
“…The synchrotron x-ray diffraction data confirmed that the present oxygen-getter-controlled low-O 2 -pressure encapsulation synthesis had yielded high-quality double-perovskite samples of [17,18], were detected. We expect that the oxygen partial pressure at the synthesis temperature, i.e.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Once the A-site ordered, oxygen-deficient (here δ ≈ 0) double-perovskite framework of Among these, the first [9,20] and the last [17,22] are close to those reported in Ref. [22].…”
Section: Resultssupporting
confidence: 83%
“…The present results are in excellent agreement with the recent experimental studies of Ln 1/2 La 1/2 MnO 3 (Ln = rareearth) by Akahoshi et al 11 and Nakajima et al 12 . In these experiments it was observed that the phase diagram has bicritical behavior (Fig.…”
Section: Influence Of Quenched Disorder On the Phase Diagram Andsupporting
confidence: 93%